Environmental Assessment of the Water of some of the Agricultural Drainage Networks of Shatt Al-Abbasiya - M. Almudhafar, Safaa; Abdullah Hassan, Hassan (International Journal of Psychosocial Rehabilitation, 2020)
Agricultural drainage is of great importance as it helps to rid the soil of salt and excess water. Agricultural drainage also regulates soil moisture, improves ventilation conditions, increases the oxygen content below the root area, and also washes the soil. There are a total of 22 agricultural drainage networks along with the specific characteristics of the water of some large agricultural drainage networks within the Shatt Al-Abbasiyah. The study found that the water of the agricultural drainage networks in the Shatt Al-Abbasiyah, all chemical elements and compounds, rises in July and decreases in January. This is due to the rise in temperature during the hot season and the high evaporation rates, adding to rice cultivation with warm climatic conditions, which increases the salts of discharged water. Some farmers use agricultural drainage water for irrigation because of water scarcity, which forced farmers to use it for irrigation, which increases the salinity of the soil and the salinity of agricultural drainage networks. It was also noted that some agricultural drainage networks are less saline than some drainage networks and are within the permissible limits for irrigation for some crops such as alfalfa and barley, especially in winter.